Repression of Nitrogen Starvation Responses by Members of the Arabidopsis GARP-Type Transcription Factor NIGT1/HRS1 Subfamily - Kiba, Takatoshi; Inaba, Jun; Kudo, Toru; Ueda, Nanae; Konishi, Mineko; Mitsuda, Nobutaka; Takiguchi, Yuko; Kondou, Youichi; Yoshizumi, Takeshi; Ohme-Takagi, Masaru; Matsui, Minami; Yano, Kentaro; et al. (The Plant cell, 2018)
Nitrogen (N) is often a limiting nutrient whose availability determines plant growth and productivity. Because its availability is often low and/or not uniform over time and space in nature, plants respond to variations in N availability by altering uptake and recycling mechanisms, but the molecular mechanisms underlying how these responses are regulated are poorly understood. Here, we show that a group of GARP G2-like transcription factors, Arabidopsis thaliana NITRATE-INDUCIBLE, GARP-TYPE TRANSCRIPTIONAL REPRESSOR1/HYPERSENSITIVE TO LOW Pi-ELICITED PRIMARY ROOT SHORTENING1 proteins (NIGT1/HRS1s), are factors that bind to the promoter of the N starvation marker NRT2.4 and repress an array of N starvation-responsive genes under conditions of high N availability. Transient assays and expression analysis demonstrated that NIGT1/HRS1s are transcriptional repressors whose expression is regulated by N availability. We identified target genes of the NIGT1/HRS1s by genome-wide transcriptome analyses and found that they are significantly enriched in N starvation response-related genes, including N acquisition, recycling, remobilization, and signaling genes. Loss of NIGT1/HRS1s resulted in deregulation of N acquisition and accumulation. We propose that NIGT1/HRS1s are major regulators of N starvation responses that play an important role in optimizing N acquisition and utilization under fluctuating N conditions.